CATHERINE’S LOVE FOR HEATHCLIFF VERSUS THAT FOR EDGAR LINTON IN “WUTHERING HEIGHTS” BY EMILY JANE BRONTE = TÌNH YÊU CỦA CATHERINE DÀNH CHO HEATHCLIFF VÀ EDGAR TRONG TIỂU THUYẾT “ĐỒI GIÓ HÚ” CỦA EMILY JANE BRONTE - Nguyễn, Thúy Hiền (2020)
It is tempting to picture “Wuthering Heights” (Bronte, 1847), the only novel of Emily Bronte, as among the greatest love novels in the cannon of literature. Not only is an ideal creation of the human brain, but the novel also is the honest reflection of theVictorian society. In “Wuthering Heights”, the readers can directly experience a number of emotions from being shocked, even being sickened by the details of cruelty, inhumanity, and the most diabolical hate and vengeance, to being obsessed by the supreme power of love. This paper will be a detailed comparison of Catherine’s love for Heathcliff and that for Edgar Linton, which has aroused a lot of criticism ever since the debut of the novel. Catherine put herself through a series of internal conflicts: Love versus social recognition to fulfil her basic needs to be happy and secure. And, the crucial part of the paper is the investigation in the Catherine’s struggling Ego in the maze surrounded by the self-desires and social constraints. Basing on Robert J. Sternberg’s The Triangular Theory of Love” and Sigmund Freud’s theory of human psyche, the writer would investigate deeply into the issues mentioned above.